Urbanization, Altitude and Cardiovascular Risk - Antonio Bernabe-Ortiz; Rodrigo M. Carrillo-Larco (Ubiquity Press, 2022)
Background: There is limited information regarding the variation of the cardiovascular (CV) risk, that combines multiple risk factors in one metric, according to urbanization and altitude. Objective: To assess and disentangle the potential association between urbanization and altitude with absolute CV risk using Peruvian nationally representative surveys. Methods: Pooled analysis of Peruvian Demographic Health Surveys (from 2014 to 2020), including subjects aged between 40 and 74 years, was conducted. The outcome of interest was the 10-year predicted absolute CV risk based on the non-laboratory version of the World Health Organization (WHO) and split into <10% and ≥10%. The exposures were urbanization (rural or urban) and altitude (<500 meters above the sea level [m.a.s.l.], between 500 and 2,499 m.a.s.l, between 2,500 and 3,499 m.a.s.l., and ≥3,500 m.a.s.l.). Crude and adjusted Poisson regression models were built to assess the associations of interest, reporting prevalence ratios (PR) and 95% confidence intervals (95% CI). Results: Data of 80,409 subjects, mean age 54.3 (SD: 8.8) and 42,640 (54.4%) females were analyzed. Regarding urbanization, 30,722 (25.4%) subjects were from rural areas, and 60.6% lives at <500 m.a.s.l., whereas only 9.3% lives at ≥3500 m.a.s.l. The 10-year predicted absolute CV risk mean was 4.5% (SD: 3.1), and 7.8% had a CV risk ≥10%. In multivariable model, urbanization, mainly rurality (PR = 0.89; 95%CI: 0.81-0.97) and altitude (PR = 0.82; 95%CI: 0.75-0.90 for those living between 2,500-3,490 m.a.s.l. and PR = 0.68; 95%CI: 0.60-0.76 for those living ≥3,500 m.a.s.l) were factors independently associated with CV risk. Urbanization was an effect modifier of the association between altitude and CV risk with a greater effect in urban settings. Conclusion: Urbanization, specifically rurality, and high-altitude, mainly ≥2,500 m.a.s.l., were factors independently associated with lower predicted CV risk.